Patients' assessment of care for type 2 diabetes: Results of the Patient Assessment of Chronic Illness Care scale in a Danish population - Anne Frølich (BMC Health Services Research, 2021)
Abstract Background The Patient Assessment of Chronic Illness Care (PACIC) scale is the most appropriate for assessing self-reported experience in chronic care. We aimed to validate the PACIC questionnaire by (1) assess patients’ perception of the quality of care for Danish patients with type 2 diabetes, (2) identify which factors are most important to the quality of care designated by the five subscales in PACIC, and (3) the validity of the questionnaire. Methods A survey of 7,745 individuals randomly selected from the National Diabetes Registry. Descriptive statistics inter-item and item-rest correlations and factor analysis assessed the PACIC properties. Quality of care was analysed with descriptive statistics; linear and multiple regression assessed the effect of forty-nine covariates on total and subscale scores. Results In total, 2,696 individuals with type 2 diabetes completed ≥ 50 % of items. The floor effect for individual items was 8.5–74.5 %; the ceiling effect was 4.1–47.8 %. Cronbach’s alpha was 0.73–0.86 for the five subscales. The comparative fit index (CFI) and the Tucker–Lewis index (TLI) were 0,87, and 0,84, respectively. Mean PACIC score was 2.44 (± 0.04). Respondents, who receive diabetes care primarily at general practice and outpatient clinics had higher scores compared to those receiving care at a private specialist. Receiving rehabilitation was followed by higher scores in all subscales. Those 70 years or older had lower mean total and subscale scores compared to younger patient groups. A higher number of diabetes visits were associated with higher total scores; a higher number of emergency department visits were associated with lower total scores. The effects of healthcare utilisation on subscale scores varied. Conclusions These results provide insight into variations in the quality of provided care and can be used for targeting initiatives towards improving diabetes care. Factors important to the quality of perceived care are having a GP or hospital outpatient clinic as the primary organization. Also having a higher number of visits to the two organizations are perceived as higher quality of care as well as participating in a rehabilitation program. Floor and ceiling effects were comparable to an evaluation of the PACIC questionnaire in a Danish population. Yet, floor effects suggest a need for further evaluation and possible improvement of the PACIC questionnaire in a Danish setting. Total PACIC scores were lower than in other healthcare systems, possible being a result of different contexts and cultures, and of a need for improving diabetes care in Denmark.